Misremembering a familiar object: mnemonic illusion, not drawing bias. - Jones, G; Martin, M (1992)
It was reported by Jones (1990) that the design of British coins is systematically misremembered. Although the Queen's head in fact faces right, most people draw it facing left. It is possible, however, that the origin of this phenomenon does not reside in memory but instead in a leftward drawing bias. Two experiments of the three reported here tested this hypothesis. In Experiment 1, British participants attempted to recall the direction of the Queen's head but responded verbally instead of pictorially. The results were similar to those of Jones and thus contradict the hypothesis that misremembering of the Queen's head is caused by a leftward drawing bias. In Experiment 2, Canadian participants attempted to draw a Canadian coin. Leftward misremembering was not observed in this case. Thus the hypothesized importance of a leftward drawing bias was again not supported. Instead, the results provided support for the schema explanation of the Queen's Head memory illusion proposed by Jones. The results of Experiment 3, which compared memory for British coins and stamps, further bolstered this conclusion.